Enantioselective Tsuji Allylations - Mohr, Justin T. (2007)
[Image: see text] The family of allylation reactions developed by Tsuji in the 1980's are capable of generating tertiary and quaternary carbon stereocenters from several synthetic precursors. Despite the utility of these transformations, they have seen little use in the synthesis of natural products. Recently, the power of these reactions has been significantly enhanced by the development of enantioselective versions of these transformations. Applications of these methods to the enantioselective syntheses of natural products and pharmaceutical compounds highlight the importance of these developments.